Nutrient use efficiency in interspecific hybrids of eucalypt - Rosim, Camila; Hsing, Tseng; Paula, Rinaldo (Revista Ciência Agronômica, 2016)
The aim of this work was to evaluate nutrient use efficiency in interspecific hybrids of eucalypt, as an aid in the development of forest breeding programs for areas with limited nutrients. To do this, five clones were evaluated at 2.25 years of age from hybrids resulting from crosses of Eucalyptus grandis x E. urophylla (C1, C2, C3, C4 and C5). The experimental design was of randomised blocks, with single-tree plots and 35 replications. For the study, four trees of average performance were cut down (replications) from each treatment (clone); the biomass, and levels and efficiency of use of N, P, K, Ca and Mg were determined in the wood, bark, leaves and branches. The data were submitted to analysis of variance and the F-test, and the means compared by Tukey’s test at 5% probability. It was found that the average for biomass allocation was greater (66.2%) for the wood, followed by the branches (13.2%), leaves (11.0%) and bark (9.6%). The C2 and C5 clones stood out as the most efficient in the use of P, Ca and Mg in the wood. The use of genotypes which are efficient in the use of nutrients is essential to the sustainability of forest ecosystems, reducing nutrient export in proportion to the biomass produced. Also, the recommendation of genotypes which are efficient in the use of nutrients for sites of poor soil fertility can optimise productivity in these locations.